Optimizing Hybrid Learning through the SPADA Platform to Enhance Pre-Service Teachers’ Higher Order Thinking Skills in Supporting the Sustainable Development Goals - Hikmawati Hikmawati; Fathurrahman Fathurrahman (Journal of Science and Science Education, 2026)
This study aims to analyze the optimization of hybrid learning through the SPADA platform in developing Higher Order Thinking Skills among pre-service teachers in the Physics Curriculum Analysis course. The study employed a quantitative approach using a descriptive research method. The participants consisted of 53 third-semester students of the undergraduate Physics Education Program, Faculty of Teacher Training and Education, University of Mataram, during the odd semester of the 2025/2026 academic year. The learning process was conducted over three months through the integration of face-to-face classroom learning and online learning using SPADA. Data were collected through a six-item essay test designed to measure higher-order thinking skills at the levels of analyzing (C4), evaluating (C5), and creating (C6). The data were analyzed using descriptive statistics, including mean score, minimum score, maximum score, learning mastery percentage, and grade distribution. The results showed that the average student learning outcome reached 87.91, with a minimum score of 83.45 and a maximum score of 88.95. The learning mastery percentage reached 100%, with 98.11% of students achieving grade A and 1.89% achieving grade B+. These findings indicate that hybrid learning is effective in developing students’ HOTS while simultaneously supporting the implementation of SDG 4 in higher education.